2014
DOI: 10.14411/eje.2014.005
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of global warming on the ground beetle (Coleoptera: Carabidae) fauna of beech forests in Bavaria, Germany

Abstract: Abstract. We studied the effects of global warming and rising temperatures on the ground beetle fauna of Bavarian beech forests using the space for time approach at two geographical scales. The first was a Bavarian-wide gradient of 50 plots in beech forests and the second a regional gradient in the Bavarian Forest in the mountains in eastern Bavaria consisting of 48 plots, which also included subalpine spruce forests. For purposes of validation, we used backdrop data from 413 additional plots all across Bavari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 18 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…In contrast, Pterostichus beetles have been shown to thrive after experimental warming (Berthe et al., ), mirroring the increased abundance and biomass of P. diligens and P. nigrita here (Figures S9 and S10). Contrasting effects of temperature have also been shown on invertebrate populations in German forests (Müller‐Kroehling, Jantsch, Fischer, & Fischer, ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, Pterostichus beetles have been shown to thrive after experimental warming (Berthe et al., ), mirroring the increased abundance and biomass of P. diligens and P. nigrita here (Figures S9 and S10). Contrasting effects of temperature have also been shown on invertebrate populations in German forests (Müller‐Kroehling, Jantsch, Fischer, & Fischer, ).…”
Section: Discussionmentioning
confidence: 88%
“…Contrasting effects of temperature have also been shown on invertebrate populations in German forests (Müller-Kroehling, Jantsch, Fischer, & Fischer, 2014).…”
Section: Invertebrate Abundance and Biomassmentioning
confidence: 91%
“…Previous studies have found clear geographical patterns in their regional diversity and assemblage composition, which have been associated with concurrently varying climate conditions (Heino & Alahuhta, ). In particular, temperature and humidity are two important environmental factors influencing the behaviour and ecology of ground beetles (e.g., Rainio & Niemelä, ), for which reason these insects are regarded as a model group for research on the effects of climate change (e.g., Müller‐Kroehling, Jantsch, Fischer, & Fischer, ). For example, temperature may influence their flight, speed of digestion, larval survival, and life‐history phenology (Butterfield, ; Lövei & Sunderland, ; Thiele, ), whereas humidity may be important in regulating behavioural patterns and habitat affinity (e.g., Kagawa & Maeto, ).…”
Section: Introductionmentioning
confidence: 99%
“…This result is congruent with fi ndings in forest systems regarding vascular plants (Walentowski & Zehm 2010) and woody plants (endemic Sorbus apomicts, Meyer et al 2005), and also with the ground Ground beetle (carabid) species positively correlated with beech dominance as derived from a CCA of the macroscale dataset (threshold r > 0.4). beetles to be found in the canopy of European beech forests (Müller-Kroehling & Zehetmair 2014). Specifi c habitat structures and habitat continuity seems to be more important for the species groups investigated than the presence or abundance of beech.…”
Section: Mesoscale Diversitymentioning
confidence: 94%